2000
DOI: 10.1016/s0005-2728(00)00180-8
|View full text |Cite
|
Sign up to set email alerts
|

Succinate: quinone oxidoreductases: new insights from X-ray crystal structures

Abstract: Membrane-bound succinate dehydrogenases (succinate:quinone reductases, SQR) and fumarate reductases (quinol:fumarate reductases, QFR) couple the oxidation of succinate to fumarate to the reduction of quinone to quinol and also catalyse the reverse reaction. SQR (respiratory complex II) is involved in aerobic metabolism as part of the citric acid cycle and of the aerobic respiratory chain. QFR is involved in anaerobic respiration with fumarate as the terminal electron acceptor, and is part of an electron transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 43 publications
3
35
0
Order By: Relevance
“…The global effects of the PAL mutations in cyt b 561 are reminiscent of results with the cytochrome b subunit of quinol:fumarate reductase from Wolinella succinogenes, where mutation of any of the four histidines predicted to be axial ligands to the hemes (69) resulted in little or no expression of the protein (70). Assignment of those histidines as axial ligands was later confirmed by crystallography (71).…”
Section: Identification Of Axial Ligands For Cyt B 561 Hemesmentioning
confidence: 91%
“…The global effects of the PAL mutations in cyt b 561 are reminiscent of results with the cytochrome b subunit of quinol:fumarate reductase from Wolinella succinogenes, where mutation of any of the four histidines predicted to be axial ligands to the hemes (69) resulted in little or no expression of the protein (70). Assignment of those histidines as axial ligands was later confirmed by crystallography (71).…”
Section: Identification Of Axial Ligands For Cyt B 561 Hemesmentioning
confidence: 91%
“…SDH, or succinate:menaquinone oxidoreductase, is another enzyme responsible for the donation of electrons to the quinone pool (13). Transposon mutagenesis confirmed that SDH is essential for survival of M. tuberculosis in vitro (24).…”
Section: Electron Donorsmentioning
confidence: 96%
“…1). Electron transport in mycobacteria is initiated through the activity of various NADH dehydrogenases (NDH) and succinate dehydrogenases (SDH), which transfer electrons to menaquinone, a lipophilic redox carrier (7,13,14). Electrons are then passed to various cytochrome oxidases, which are dependent on oxygen availability ( Fig.…”
Section: The Mycobacterial Etcmentioning
confidence: 99%
“…The ability to reduce hydrophobic quinones is conferred to the enzyme by a so-called membrane anchor subunit, whose structure and composition can vary significantly in different organisms (14,38). In B. subtilis, this subunit is a diheme cytochrome b (15), with the two porphyrin groups arranged across the membrane on top of each other, as predicted by mutagenesis studies (14,16) and confirmed recently by the three-dimensional crystal structure of complex II from Wolinella succinogenes (32,34). The low-potential heme b (approximately isopotential with MQ-MQH 2 [15,50]) is located close to the outer periplasmic side of the membrane and is believed to be the MQ reducing site (20,39,42,47,50).…”
mentioning
confidence: 83%
“…It is noted that the hypothesis of vectorial electron transfer through SQR is not necessarily compromised by our results. The membrane potential-driven reduction of MQ in B. subtilis SQR is predicted explicitly by the structure of the enzyme and therefore remains an attractive possibility (14,32,42), which, however, should not be confused or identified with the effect of energy-dependent stimulation of respiration.…”
mentioning
confidence: 99%